DETERMINANT FACTOR OF LOCAL FOOD CONSUMPTION OF THE HOUSEHOLDS IN LAMPUNG PROVINCE - Wuryaningsih Dwi Sayekti, (Perum BULOG, 2020)
Diversification of food consumption is an effort to realize food security. Diversification of food consumption must be based on the potential of local resources, so the development of processed local food is important. Tapioca vermicelli and siger rice are local food preparations that are widely known by the people of Lampung Province as a substitute for carbohydrate sources of tubers. This research addresses to determine consumption and identify determinants of household local food consumption. The study was conducted in Bandar Lampung City, Metro City, and Pringsewu District, Lampung Province using survey methods. The research location was selected purposively. The research sample consisted of 180 households who were selected randomly. Data was collected by interviews with questionnaires. Data was analyzed by descriptive and factor analysis. The results showed that cassava is the most consumed local food. Based on the 14 factors analyzed, formed five factors, namely the recognition and acceptance factors, nutritional knowledge, education, wive’s job, and the number of household members. The factor of consumer recognition and acceptance of local food was a determinant factor of local food consumption in Lampung Province.